Portfolio of compositions (and accompanying commentary) - Kolassa, Alexander (2015)
The first half of this commentary/thesis will explore changing perceptions of the musical work and the creative process. Ultimately, it will seek to identify and expose the myth of what we might call the ‘tyrannical composer’. That is to say, a suspicion of what is implied hierarchically by the figure of the composer and the consequences this has on critical thought, scholarship, performance and the public perception of music, new and old.